α-Alkylation of (S)-Glyceric Acid through the tert-Butylthioester of (2R,4S)-2-tert-Butyl-1,3-dioxolane-4-carboxylic Acid - Dieter Seebach; Marlyse Coquoz (CHIMIA)
The thioester (9) mentioned in the title is prepared in three steps from (S)-serine. Deprotonation with LiN(CHMe2)2 generates a chiral enolate (10) which is alkylated preferentially from the Re-face (cis to the tert-butyl group), to give products of type 11. Possible reasons for the steric course of the reaction of the thioester enolate (relative topicity lk, see 13) and the value of the products thus available as synthetic building blocks with a persubstituted, OH-functionalized asymmetric carbon atom (see 4, 5, 6) are discussed.